Referendums and ethnic conflict - Qvortrup, Matt (University of Pennsylvania Press, 2022)
This updated and revised edition of Referendums and Ethnic Conflict features recent referendums, including Scotland (2014), Catalonia (2017), and the Brexit vote in the United Kingdom (2016), among others, through 2020. The book's political framework also addresses new developments such as identity politics, social media, and populism.